Ethanol improves lipase immobilization on a hydrophobic support - Blanco Martín, Rosa María; Terreros Ceballos, Pilar; Muñoz, Núria; Serra, Elías M. (Elsevier, 2007)
A mesoporous silica functionalized with octyl groups had been used as the support for lipase (from Candida antarctica) immobilization. The hydrophobicity provided by the hydrocarbon chains together with the excellent morphologic characteristics of the solid leads to high enzyme loadings in monolayer fashion. However, in this kind of systems the aqueous enzyme solution cannot easily access all the inner surface of the pores because of the highly hydrophobic nature of these surfaces. Thus, the presence of low ethanol concentration decreases the hydrophobicity of the channels and the access of enzyme seems to be significantly improved. The monolayer capacity (400–500 mg protein/g of octyl silica) increases twice compared to the corresponding immobilization in the absence of ethanol (200 mg protein/g of octyl silica). The activity of the derivatives prepared in the presence of ethanol was also significantly improved: 33,000 tributyrin units/g of catalyst at the monolayer limit, which is four- to five-fold higher than the activities of the corresponding derivatives prepared in the absence of ethanol. This work was possible thanks to the financial support from Spanish Ministerio de Educacion (project AGL2004-07227-C02-01). Elías Serra acknowledges the support of a Comunidad de Madrid PhD fellowship.